Peran Hukum Kesehatan dalam Penyelenggaraan Pelayanan Kesehatan di Indonesia pada Layanan Telemedicine - Juliansyah Yugis Saputra; Dyah Ersita Yustanti (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2026)
The development of information technology has triggered significant changes in the Indonesian healthcare system, including through the implementation of telemedicine as a key innovation. This digital health innovation requires strengthening the role of health law to ensure service quality, patient safety, and legal guarantees for healthcare workers and service providers. This paper aims to examine the function of health law in the management of national healthcare services, with a particular focus on telemedicine healthcare services, and to evaluate the suitability of its regulations in protecting patient rights. The methodology used is normative legal analysis, which involves examining various laws and regulations such as Law Number 72 of 2023 concerning Health, Law Number 8 of 1999 concerning Consumer Protection, and Regulation of the Minister of Health Number 20 of 2019 concerning the Implementation of Telemedicine Services. Supporting data was obtained from reviewing national scientific journals, which discuss aspects of health law and telemedicine in Indonesia. The results of the study indicate that health law functions as a mechanism to regulate service standards, protect patient rights, and oversee the accountability of healthcare workers in telemedicine practices. However, the implementation of regulations related to telemedicine still faces several obstacles.